Doctor's Responsibility for Delegation of Authority to Nurses that Cause Unexpected Events - Sanusi, Sanusi; Setiadi, Asep Subur (International Journal of Social Service and Research, 2024)
Health, recognized as an essential entitlement for every individual according to the 1945 Constitution of the Republic of Indonesia, holds substantial implications for community well-being. Article 28 H paragraph (1) upholds the entitlement of all individuals to health services, with the state being accountable for ensuring the availability of sufficient public service facilities. Nevertheless, the scarcity of physicians and healthcare professionals in Indonesia poses challenges to health services, particularly evident in the low ratio of doctors per 1000 population. Collaboration between doctors and nurses is imperative, with the delegation of authority serving as a form of joint action. However, understanding the legal aspects of authority delegation often proves to be an intricate matter in this professional relationship. This study aims to explore the practice of handing over physicians to nurses at Rajagaluh Health Center and the factors that influence its implementation. With a legal approach and positivism paradigm, this study uses qualitative descriptive methods with primary data from the Rajagaluh Health Center and secondary sources from books, journals, websites, and related research. The research instrument focused on medical record analysis to collect data related to the practice of delegation of authority, influence factors, and responsibilities of doctors for unexpected events. The study aims to contribute theoretically to the advancement of science, particularly in the realm of health law. Simultaneously, it endeavors to enhance practical comprehension regarding the delegation of authority between doctors and nurses, along with offering a comprehensive perspective on patient safety within